2019
DOI: 10.1186/s12875-019-1051-3
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle behaviours in patients with established cardiovascular diseases: a European observational study

Abstract: BackgroundPatients who have experienced a cardiovascular clinical event such as a myocardial infarction or stroke qualify for intensive risk factor evaluation and management.The aim of this study is to explore lifestyle changes as well as the achievement of targets for risk factors in patients with established cardiovascular disease.MethodsCross-sectional study conducted in primary care practices. The study was carried out in six European countries (Croatia, France, Portugal, Slovenia, Spain and Turkey). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Variables that are shown to be important for PA and/or stroke outcome were assessed in the study; including age (24), sex (26), smoking status ("yes" corresponds with ≥ 1 cigarette/day, or quit during the last 3 months) (27), previous cerebrovascular disease (CVD) ("yes" corresponds to diagnosis of at least one of the following diseases prior to stroke: heart failure, ischaemic heart failure, hypertension, angina, hypercholesterolaemia, aortic insufficiency, atrial fibrillation, myocardial infarct, prosthetic heart valve, or rheumatic valvular heart disease) (27), living arrangements ("living alone" or "sharing household with another adult") and occupational status ("working" ≥75% fulltime work, or "not working" <75%) (28).…”
Section: Methodsmentioning
confidence: 99%
“…Variables that are shown to be important for PA and/or stroke outcome were assessed in the study; including age (24), sex (26), smoking status ("yes" corresponds with ≥ 1 cigarette/day, or quit during the last 3 months) (27), previous cerebrovascular disease (CVD) ("yes" corresponds to diagnosis of at least one of the following diseases prior to stroke: heart failure, ischaemic heart failure, hypertension, angina, hypercholesterolaemia, aortic insufficiency, atrial fibrillation, myocardial infarct, prosthetic heart valve, or rheumatic valvular heart disease) (27), living arrangements ("living alone" or "sharing household with another adult") and occupational status ("working" ≥75% fulltime work, or "not working" <75%) (28).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, among the 84% that were on lipid-lowering drugs, up to 68% of them were not at target LDL-c <70 mg/dl ( 8 ). Another European cross-sectional study conducted in 973 patients with established CVD (coronary heart disease (CHD) and stroke) being attended in primary care showed that LDL-c target value below 70 mg/dl was achieved in about 23% of patients, and about 75% of patients reached the <140/90 mmHg target for BP ( 37 ).…”
Section: Secondary Prevention In Chronic Cardiovascular Diseasementioning
confidence: 99%
“…Health behaviours that positively influence human health-apart from one's self-control, responsibility for one's own health, and a positive attitude-are mainly a healthy diet, regular physical activity, and an adequate amount of sleep per day. Disease risk factors and thus negative health behaviours include smoking, incorrect diet, low or no physical activity, and alcohol abuse [4,5,[11][12][13]. The unsatisfactory health situation of the Polish population, with a tendency to deteriorate in some spheres, requires specific health and preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…The unsatisfactory health situation of the Polish population, with a tendency to deteriorate in some spheres, requires specific health and preventive measures. The study and analysis of health behaviours create an opportunity to diagnose the areas of ignorance in the field of health care, to determine the risks and harmfulness, as well as to determine the scale of the problem in order to prevent irregularities or pathologies [4,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation